Neurocognitive Narratives and Cultural Conflicts: A Transdisciplinary Analysis of Socioeconomic and Cultural Intersections in Contemporary American Literature - Feiz, Manzar; JAMALPOUR, HAMED; Jamalpour, Zahra; Habibi, Elham; Habibi, Aref; Hosseinzadeh, Nasim; Khozoee, Soheilasadat (Cultural Conflict and Integration, 2025)
This descriptive study examines how contemporary American literary texts intertwine neuroscience, psychiatry, economics, and cultural studies to explore cognitive, emotional, socioeconomic, and cultural dimensions of human consciousness. Analyzing narrative structures in works like Ocean Vuong’s Night Sky with Exit Wounds, Colson Whitehead’s The Nickel Boys, and Carmen Maria Machado’s In the Dream House, it identifies “narrative cognitive patterns” that mirror neural processes while reflecting cultural conflicts, such as Native American marginalization in Tommy Orange’s There There or immigrant identity tensions in Vuong’s poetry. Texts such as Phil Klay’s Missionaries, Ling Ma’s Severance, Patricia Lockwood’s No One Is Talking About This, and Jesmyn Ward’s Salvage the Bones portray mental health challenges, trauma, depression, shaped by economic instability (post-2008 recession, digital economies) and cultural dislocation. Synthesizing interdisciplinary scholarship, the study proposes a “neuroeconomic-cultural narrative model” to examine brain, mind, economy, and cultural integration. This framework highlights how narratives bridge cultural divides, fostering mutual understanding across diverse identities (e.g., Native vs. mainstream, immigrant vs. native-born). The inquiry invites global explorations of literature’s reflection of cognitive, socioeconomic, and cultural realities, offering insights for bibliotherapy and cultural policy. This study’s transdisciplinary approach, grounded in rigorous scholarship, invites further exploration of how literature reflects cognitive, socioeconomic, and cultural realities, paving the way for global comparisons and practical applications like bibliotherapy or cultural policy.